Pitu Ba’bana Binanga: The Diplomatic Legacy of the Balanipa Kingdom in Harmonizing Politics, Religion, and the Economy of Mandar - A. Nurkidam; Usman Usman; Najmu Zakib; Hasmiah Herawaty (Universitas Hamzanwadi, 2026)
This study analyzes the diplomacy of the Balanipa Kingdom in managing political, religious, and economic relations within the Mandar context, particularly through the Pitu Ba’bana Binanga confederation mechanism (seven kingdoms at the river mouth). This study employs a qualitative historical method combining literature review, in-depth interviews, and primary source analysis. This study finds that Balanipa’s diplomacy was not merely an instrument of external relations, but an internal consolidation mechanism that integrated the political dimension through deliberation and collective governance structures, the religious dimension through accommodative Islamization and the institutionalization of Sharia within the Parewa Saraq, and the economic dimension through the management of an inclusive maritime trade network. Key findings indicate that the cultural values of sipamandar (mutual reinforcement) and sirumung karaya (consultation) serve as the philosophical foundation shaping the character of Balanipa diplomacy—which is non-aggressive, participatory, and oriented toward multilateral harmonization. This diplomatic model holds significant relevance for contemporary social and multicultural development, particularly in strengthening participatory democracy, managing diversity based on local consensus, and revitalizing local wisdom in the era of globalization.